Zona Pengembangan Usaha Mikro Kecil dan Menengah (UMKM) Pengolah Makanan di Kota Bekasi: The Development of Food Processing Centers for Micro, Small and Medium Enterprises (MSMEs) Zone in Bekasi City - Fitri Insani; Baba Barus; Djuara P. Lubis (P4W LPPM IPB, 2021)
Micro, Small and Medium Enterprises (MSMEs) have very significant contribution to the growth and development of the economy of Bekasi City with a total of approximately 203,000 units. The large number of food processing MSMEs in Bekasi City has not been accompanied by the formation of a spatially integrated MSMEs center zoning. This research aims to understand the spatial distribution and the determination of the zones of food processing MSMEs in Bekasi City. The research was conducted in Bekasi City during February-August 2019. Data were obtained through data tracing from related agencies, field observations, and interviews with experts. Analytical methods include Analytical Hierarchy Process (AHP) to determine the weight of each parameter, and Multi Criteria Evaluation (MCE) for determining development centers. Analysis shows that the number of selected MSMEs was 220 samples, with the highest number of MSMEs in Pondok Gede District. Food processing MSME development zones in Bekasi City are divided into three development zones, namely development zone 1, development zone 2, and development zone 3. Development zone 1 and development zone 2 are the best zones located in West Bekasi District, Jatiasih District, and Jatisampurna District. Development Zone 2 consists of North Bekasi District, Medan Satria District, Pondok Gede District, and Pondok Melati District because the two zones are adjacent to Jakarta City. Meanwhile, development zone 3 should receive special attention, consisting of Bantar Gebang District, South Bekasi District, East Bekasi District, Mustika Jaya District, and Rawalumbu District.